A scoping review to map the implications of reusing single-use endotracheal suctioning catheter practices in mechanically ventilated patients - Eid, Mohamed H.; Hambridge, Kevin; Schofield, Patricia; Latour, Jos M. (Intensive & critical care nursing, 2025)
Currently there is limited evidence of the frequency of using endotracheal suctioning catheters. Due to limited resources, many low- and middle-income countries still reuse single-use suction catheters multiple times during the length of a nursing shift. This scoping review was conducted to map the impact of reusing single-use endotracheal suctioning catheters practices on mechanically ventilated patients’ outcomes. The scoping review was conducted in accordance with the JBI methodology for scoping reviews. Four databases systematically searched using predefined keywords (CINAHL, EMBASE, MEDLINE, GLOBAL HEALTH). Key electronic journals were hand searched, while reference lists of included documents and grey literature sources were screened thoroughly. Two independent reviewers completed the study selection and data extraction. A third reviewer made the final decision on any disagreements disputed records. In total 22 articles were identified, and 14 non-duplicate records were screened, and 8 articles were screened for full text. Six articles met the inclusion criteria and were included in this review. Differences were observed on the findings of included studies, two studies identified that reusing single-use suction catheter might increases the risk of respiratory infection, while two other studies identified no difference in contamination rate between single used or multiple-used catheters. One study indicated that reusing single-use catheters are a safe and cost-effective intervention and finally one study reported that reusing single-use catheters might reduce incidence of ventilator associated pneumonia if flushed with chlorhexidine after suctioning. There is no strong evidence of the frequency of using endotracheal suction catheters. Further research is needed comparing single-used versus multiple-used endotracheal suction catheters in mechanically ventilated patients. Nurses in resource-limited countries can follow their hospital policy regarding the changing frequency of endotracheal suction catheters due to lack of a robust evidence. Flushing suction circuits with chlorhexidine while reusing single-use catheters might reduce the risk of respiratory infections in these hospitals.